Correction: Is serum level of CC chemokine ligand 18 a biomarker for the prediction of radiation induced lung toxicity (RILT)? - Eleni Gkika; Werner Vach; Sonja Adebahr; Tanja Schimek-Jasch; Anton Brenner; Thomas Baptist Brunner; Klaus Kaier; Antje Prasse; Joachim Müller-Quernheim; Anca-Ligia Grosu; Gernot Zissel; Ursula Nestle (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0185350.].